Decision Support Alerts for Medication Ordering in a Computerized Provider Order Entry (CPOE) System - Del Beccaro, M. A.; Villanueva, R.; Knudson, K. M.; Harvey, E. M.; Langle, J. M.; Paul, W. (Applied Clinical Informatics, 2010)
Objective: We sought to determine the frequency and type of decision support alerts by location and ordering provider role during Computerized Provider Order Entry (CPOE) medication ordering. Using these data we adjusted the decision support tools to reduce the number of alerts.Design: Retrospective analyses were performed of dose range checks (DRC), drug-drug interaction and drug-allergy alerts from our electronic medical record. During seven sampling periods (each two weeks long) between April 2006 and October 2008 all alerts in these categories were analyzed. Another audit was performed of all DRC alerts by ordering provider role from November 2008 through January 2009. Medication ordering error counts were obtained from a voluntary error reporting system.Measurement/Results: Between April 2006 and October 2008 the percent of medication orders that triggered a dose range alert decreased from 23.9% to 7.4%. The relative risk (RR) for getting an alert was higher at the start of the interventions versus later (RR= 2.40, 95% CI 2.28-2.52; p< 0.0001). The percentage of medication orders that triggered alerts for drug-drug interactions also decreased from 13.5% to 4.8%. The RR for getting a drug interaction alert at the start was 1.63, 95% CI 1.60-1.66; p< 0.0001. Alerts decreased in all clinical areas without an increase in reported medication errors.Conclusion: We reduced the quantity of decision support alerts in CPOE using a systematic approach without an increase in reported medication errors
Keywords: Computerized provider order entry; CPOE; clinical decision support; alert fatigue